Formulation of cosmetic creams containing centella asiatica L. and aloe vera (L.) burm. F. herbal extracts in nanoemulsion system - Shafii, Ziti Akhtar (2011)
osmetic creams containing Centella asiatica (pegaga) and Aloe vera (lidah buaya) extracts were formulated at 20%and 40% (w/w) oil-in-water (o/w) nanoemulsion systems using various concentrations (5.2%, 7.2% and 9.2% w/w) of mixed nonionic surfactant (Span 80/Tween 80 at 20:80 w/w ratio). The nanoemulsions were prepared using a spontaneous emulsification method. The physicochemical properties of the cosmetic creams were characterized by particle size analyzer, surface charge measurement (zeta potential) and thermodynamic stability tests. The antioxidant activity of the nanoemulsions was determined by a diphenylpicril hydrazyl (DPPH) scavenging method. Meanwhile, the moisturizing effects of 20% and 40% nanoemulsion cosmetic creams with and without herbal extracts on human skin were characterized using a Cutometer and Tewameter to determine the water content and percentage of water loss in the stratum corneum respectively. The rheological properties of the creams in the presence of xanthan gum as a thickening agent were characterized. The morphological properties of the cosmetic creams products were investigated by Transmission Electron Microscopy. Results showed that, the particle sizes of fresh and stored samples were constant within the nanosize range which was less than 200 nm measured for up to 4 months after preparation. They were significantly stable nanoemulsions. However, the formulation containing 40% oil-inwater using 5.2% (w/w) of surfactant gave a slightly bigger droplet size, ranging from 490 nm to 510 nm. The surface charge measurements or zeta potential of the 20% oil-inwater nanoemulsions varied from -26 mV to -37 mV indicated formation of very stable nanoemulsions creams. The presence of excess oil (40% oil-in-water) significantly influenced the surface charge values where the zeta potential shifted to very low values between -38 mV to -48 mV and the creams became more stable. All of the nanoemulsion cosmetic creams showed a good thermodynamic stability (measured by observing the physical appearance) at 5°C, 25°C and 45°C. The nanoemulsion creams produced did not interfere the antioxidant activity of C. asiatica. Thus, the nanoemulsion systems which are used as an antioxidant carrier in this study have no effect on the antioxidant activity of the cosmetic creams. A combination of C. asitica and Aloe vera extracts has potential to be used as moisturizing agent and as a barrier on the skin to prevent water loss into the air. The presence of xanthan gum significantly influenced the viscosity and stability of the nanoemulsion creams. The nanoemulsion creams showed a non-Newtonian or shear thinning fluid behaviour where the viscosity decreased with increasing shear rate. Morphological behaviour of the nanoemulsions as evaluated by a Transmission Electron Microscope showed that the oil droplets appeared dark against a bright background and the particle size (100 to 500 nm) was within the range determined by the Nanophox particle analyzer. As a conclusion, crude herbal extracts can be added into nanoemulsion cosmetic creams without interfering the creams stability and at the same time maintaining their functional properties.